2005
DOI: 10.1111/j.1432-2277.2004.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection against acute porcine lung ischemia/reperfusion injury by systemic preconditioning via hind limb ischemia

Abstract: Summary Previous work on various organs and tissues has shown that ischemic preconditioning protects against reperfusion injury in these organs and also against secondary effects in the lung. In contrast, the purpose of this study was to investigate the effects of preconditioning in a remote organ (hind limb ischemia) on an ischemia/reperfusion (I/R) treatment of the lung itself. A porcine model of in situ left lung ischemia (90 min) and reperfusion (5 h) was used. Systemic preconditioning was induced by clamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 24 publications
1
28
0
3
Order By: Relevance
“…Attenuation of lung IRI damage in a porcine model of lung IRI could be achieved by brief, repeated phases of sublethal ischemia to the hind limb skeletal muscle (19). The results showed that functional characteristics of lung IRI were completely reversed; however, the brief ischemia to the hind limb was not sufficient to completely ameliorate the systemic inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…Attenuation of lung IRI damage in a porcine model of lung IRI could be achieved by brief, repeated phases of sublethal ischemia to the hind limb skeletal muscle (19). The results showed that functional characteristics of lung IRI were completely reversed; however, the brief ischemia to the hind limb was not sufficient to completely ameliorate the systemic inflammation.…”
Section: Discussionmentioning
confidence: 98%
“…During surgery of the lower limbs, there is release of cytokines after prolonged limb ischemia leading to acute respiratory distress syndrome and limb preconditioning could protect against lung dysfunction found with acute respiratory distress syndrome. (2) RIPC by left femoral artery occlusion (3 ϫ 5 min) prior to lung IRI (90 min ischemia, 5 h reperfusion) [59] in a porcine model reversed the detrimental effects of lung IRI on lung function and attenuated pulmonary hypertension and impaired gas exchange. Thus, both models of RIPC [58].…”
Section: Role Of Mesenteric Ipc (Table 4)mentioning
confidence: 99%
“…RIPC also protects other organs such as brain, lung, liver, and kidney [1,2,4,11,19,24,25]. Recently, RIPC has been brought from the bench to the operating theater.…”
mentioning
confidence: 99%